Solitary colonic neurofibroma in an African child (2018)
Neurofibromas are a group of heterogeneous neurocutaneous disorders. They are benign neoplasms consisting of neural and connective tissue components affecting any organ system. Gastrointestinal involvement in neurofibromatosis type 1 (NF1) are rare and are late manifestations of the disease, but in exceptional cases they can be the initial sign of neurofibromatosis in patients who have no external stigmata that arouse suspicion. Neurofibromatosis of the colon as a part of the NF1 is rare. Isolated colonic neurofibromatosis without other features suggestive of NF1 is rarely encountered in clinical practice. We report the case of a 12-year-old boy with an isolated colonic neurofibromatosis presenting with a right hypochondrial mass with no external features of NF1. We report this case as its presentation in children may give a diagnostic dilemma and the probability of malignant digestive disease associated with NF1 should be kept in mind, regardless of the age of the patient.